Ali b. Nâsır el-Hicâzî’nin Kitâbü’t-tahrîcâti’l-muhtasara li’l-ehâdîsi’lmüştehera isimli eserinin tahkik ve tahlili - Öztürk, Enes (My University, 2024)
Hadis edebiyatının önemli bir türü olan tahrîc, hadisleri ihtiva eden herhangi bir eser ile asli hadis kaynakları arasında ilişki kurması bakımından bir tür denetim mekanizması işlevi görür. Tahrîcdeki temel amaç, çeşitli İslâmî ilimlere dair eserlerdeki hadislerin tesbiti, bunların isnadı ve metninin değerlendirilmesidir. Tarihi süreçte bu amaçla yapılan çalışmaların en önemlilerinden biri de Sehâvî’nin elMakâsıdü’l-hasene isimli eseridir. Bu eser üzerinde yapılan ihtisar çalışmalarının ilki sayılabilecek ve aynı zamanda tez konumuz olan eser, bizatihi Sehâvî’nin talebesi Ali b. Nâsır el-Hicâzî’nin (v. 916/ 1510-11 de hayattaydı.) ET-TAHRÎCÂTÜ'LMUHTASARA Lİ'L-EHÂDÎSÎ'L-MÜŞTEHERA isimli çalışmasıdır.Yazarı Sehâvî’nin el-Makâsıdü’l-hasene kitapından daha küçük ve kısa bir şekilde bize sunmüştür. el-Hicâzî’nin et-Tahrîcât’ı hem el-Makâsıd’ın ilk muhtasarı olması, hem de bugüne kadar tahkikli bir neşrinin yapılmamış olması hasebiyle dikkatimizi çekmiştir. Bu itibarla genel olarak senedlerin hazfi, Sehâvî’nin ayrıntılı izahlarına yer vermemesi ve tahricde ilave kaynaklar zikretmesi gibi özellikleri bulunan bu muhtasarın, tahkikinin yapılarak matbu hale getirilmesinin hadis ilminin literatürüne önemli bir katkı sağlayacağı tespit edilmiştir. Sehâvî’nin kitabı, bu konuda yazılmış en önemli eserlerden biridir ve telebesi elHicâzî’nin muhtasarı, Sehâvî’nin kitabının ünlü bir kitap olmasından önem almıştır ve bu ilimde uzman bir alim tarafından yazılmıştır. Bundan birkaç sonuç çıkarıyoruz : -Hicazi'nin henüz ışığı görmemiş kitaplarına, ve özellikle kütüphanelerin henüz kimse görmemiş eserler le ile dolu Sünnet kitaplarını yayınlamak bize düşer. -Memlûk devleti devrinde(Hicazinin bütün şeyhleri göz önünde bulundurarak) ilmin refahının nedenini incelemektir. et-Tahrîcât’ın tahkikinde esas alınan aslî nüsha, Nuruosmaniye Kütüphanesi’nde yer almakta olup 103 varaktan, her varak da ortalama 20 ilâ 27 satırdan ve her satırı da ortalama 15 kelimeden oluşmaktadır. Varakların eksiksiz ve hattının okunaklı olması bakımından gayet iyi durumda olan bu nüsha, müellifin vefatından yaklaşık iki asır sonra 1136 senesinde müstensih Ali b. Sâlim ed-Demâtî el-Mâlikî’nin hattıyla istinsah edilmiştir. Tahkikte mukabele edilecek ancak üzerinde herhangi bir tarih kaydı bulunmayan diğer bir nüsha ise aslî nüshaya göre daha kötü durumdadır.

The science of Tahrig is an important science with a high status, because it is the basis of knowledge of the Prophet’s Sunnah, on which the understanding and interpretation of the Qur’an revolves. Likewise, on it the orbit of rulings and their details, and through it the lawful and the forbidden are known, and so on, and the most important fruit of the principles of graduation is preserving and preserving the Sunnah from the intruder to it and knowing the correct hadiths from their weak and other rulings related to the knowledge of the honorable hadith. This is not clear except by collecting and examining all the hadith methods, and among its benefits is also knowing the meaning of the hadith in its original sources. Among its benefits is also that we stand on the words of the imams in the hadith whether they are weak or correct, so it is easy for us to judge the hadith, and by examining its methods also, the evidence for the hadith becomes clear to us from the hadiths and methods. The other, and we may stand on the reasons for the occurrence of the hadith by collecting its methods and graduating it, and we can also know the meanings of the stranger from it, as it may become clear in one of the narrations the intended meaning of the hadith. The subject of our thesis is the investigation of the book Al-Takhrijat alMukhtareej by Ali ibn Nasir al-Hijazi, which is a summary of al-Sakhawi’s book called al-Maqasid alHusna in explaining many of the well-known hadiths on the tongues. Tongues And he investigated as a master's thesis at the University of Sana'a in Yemen, including Ibn Al-Diba' in his book Distinguishing the good from the bad from what is going on in people's tongues from the hadith also from his abbreviations and he has other abbreviations as well. The most famous one who benefited from Al-Sakhawi's book is Al-Ajlouni in his famous book Kashf Invisibility and removing clothing from what is well-known on people’s tongues.” And it was mentioned in his introduction that he shortened it by omitting its chains of transmission and leaving the lengthy ones in it with the addition to it of other hadiths from the books of the respected imams. Al-Hafiz al-Sakhawi, whose author mentioned that he abbreviated it from the book al-Maqasid al-Hasanah by his sheikh by omitting chains of narration and lengthening it in many places, and perhaps he brought benefits to the book by deleting, adding, excluding or objecting to the author of al-Maqasid. His sheikh Al-Sakhawy translated for him in his book Al-Daw’ Al-Lama’, as well as Ibn Al-Imad in “Nuggets of Gold” in “Akhbar Min Dahab” and “Al-Ghazi” in “Al-Kawakeb Al-Sa’irah”, all of which are brief translations that do not give a clear picture of the details of his life. And the version that I relied on in my investigation of this book is the copy of the Noor Ottoman Library, consisting of 103 papers, between 20 to 27 lines in the middle, with 15 words in the middle. The copy that I am interviewing is a copy that does not have a date and is a poor copy in relation to the original copy. In the study section, I will introduce the science of graduation, explain its subject, the origins of blogging in it, and the works that I wrote about it, then I will talk about this book of ours and its origin in terms of its name, subject, method of its author, the scholars’ care for it, and the differences between the two books, then I will mention the author’s translation with what he needs of scientific analysis and criticism.
دراسة وتحقيق كتاب التخريجات المختصرة لألحاديث المشتهرة لعلي بن ناصر الحجازي
Keywords: dirase; Hadis; Hadith; Hicazi; ihtisar; müştehir; Nasser al-Hejazi; Studying and investigating- al-takhrigat al-mukhtasara- Ali bin; tahkik; tahric